(3GdCbUi GdbQjHs - (3GdJfhNj , eMeO Hf eMeO Hf eMeO Hf YeQ, Rjf GdOjf CHh YHO Gddgs
(3ChdgG (B:s
(3hHYO aEfi CdaJ gPG GdeNJUQ ai Yde GdHjGf abdJ s
(3BNQgG (B:s
(3ai bJdg TQYkG hCeG eMeO GdJfhNi eDda GdcJGH GdePchQ s
(3Vef eLehY s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B286s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3HdGZI JjehQ (B104) s
Keywords: (3GdHdGZIs